We first : how brands and consumers use social media to build a better world - Mainwaring, Simon. 1967- (New York : Palgrave Macmillan, 2011)
A social media expert with global experience with many of the world's biggest brands --including Nike, Toyota and Motorola--Simon Mainwaring offers a visionary new practice in which brands leverage social media to earn consumer goodwill, loyalty and profit, while creating a third pillar of sustainable social change through conscious contributions from customer purchases.
Transforming the engine of capitalism -- Redefining self-interest from me first to we first -- The future of profit is purpose -- Creating sustainable capitalism in five ways -- Instilling we first values into capitalism -- Why the world needs a responsible private sector -- How brands build their business and a better world -- How consumers build responsible brands and a better world -- How contributory consumption creates sustainable social change -- The global brand initiative : the future of the private sector.
Includes bibliographical references (p. [233]-244) and index.
Keywords: Social responsibility of business; Capitalism; Social media -- Economic aspects; Branding (Marketing).; Internet marketing